ZISWAF'S Role as Community Empowerment Through One Family One Graduate Scholarship at Baitul Mal Aceh - Muksal, Muksal; Arifin, Muhammad; Aspira, Muizatul (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Community empowerment through the One Family One Bachelor (SKSS) scholarship is a program that has the potential to develop society both economically, personally and socially. Therefore, this research examines community empowerment and its mechanisms and optimization. The purpose of this research is to determine the mechanism and optimization of community empowerment through SKSS scholarships at Baitul Mal Aceh. This research uses qualitative research methods with a field research approach. The research results show that the mechanism for community empowerment through the SKSS scholarship includes the objectives of the stages and the benefits obtained, where this mechanism is still not well realized. So the optimization of community empowerment through SKSS scholarships is seen from three dimensions of optimization, namely efficiency, effectiveness and economics, which are described by several indicators, which are still classified as less than optimal, because of the many obstacles and obstacles faced and the output that has not been achieved. However, on the other hand, Baitul Mal Aceh is currently trying to carry out an evaluation, designing a new, better system which is expected to optimize community empowerment through SKSS scholarships in the future.